DIAMETER DISTRIBUTION OF Araucaria angustifolia (Bert.) O. Ktze. IN A FRAGMENT OF MIXED OMBROPHYLOUS FOREST - MACHADO, Sebastião do Amaral; AUGUSTYNCZIK, Alan Lessa Derci; NASCIMENTO, Rodrigo Geroni Mendes; FIGURA, Marco Aurélio; da SILVA, Luís César Rodrigues; MIGUEL, Eder Pereira; TÉO, Saulo Jorge (Scientia Agraria, 2009)
The objective of the present research was to evaluate the behavior of probabilistic density functions for fitting of Araucaria angustifolia diameter distribution taking in account 3 different class intervals. The data used for fitting the functions came from a complete enumeration forest inventory of a Mixed Ombrophylous Forest fragment with 15.24 ha, located at the Campus III of the Federal University of Paraná. The diameters of 341 araucárias trees were measured at 1.3 m (DBH). The following probabilistic density functions were fitted: Normal, Log-Normal, Gamma, Beta, Weibull 3P, Weibull 2P and Sb of Johnson. The diameter class intervals of 2 cm, 5 cm and 6.55 cm were tested. The results of the Kolmogorov-Smirnov test indicated that the most efficient function for class intervals with amplitude of 6.55 cm and 2 cm was the Normal and for amplitudes of 5 cm the Sb function was the best one. The Weibull 2P function was rejected by the Kolmogorov-Smirnov adherence test for all diameter class intervals adopted. This research also indicated that the Araucaria angustifolia diameter distribution is symmetric and platicurtic.